Plant communities on bedrock outcrops in the north-western part of the Stavropol Upland - Viktor Nikolaevich Belous; Maxim Jurevich Kukharuk (Наука. Инновации. Технологии)
The article reflects the results of studies on stony communities of Upland Stavropol's steppe landscapes. The floristical and ecological structure of the phytocoenoses on calcareous bedrock are discussed. As a result of the floristic studies in 2015-2016, we found out the modern stony steppes's flora consists of 151 higher plant species. We registered 12 distinctive sites. Also the phytocoenotic table and the characteristics of the communities are represented; their vegetation structure has been described. Species's abundance, distribution of relief elements and communities determined by the expert on the basis of field information. Both the perculiarities of communities and the factors of their spatial differentiation have been characterised. The main factors that influence the development of vegetations in question are abrasion and denudation processes. The petrophytic steppes are formed by limestone in the studied area. The plant communities occur on rocky slopes with poor integrity of bed-rock and development of soil cover, high insolation and low moistening of the ecotope. The petrophytic communities differ in the range of species, including rare and endangered ones such as: Medicago cancellata, Iris pumila, Orchis tridentata, Crocus re-ticulatus, Scabiosa isetensis, Thymus daghestanicus, Euphorbia glareosa, Gypsophila glomerata, Polygala sosnowskyi, Psephellus annae, Linum tauricum, Salvia nutans, Hedysarum bieberstei-nii, Artemisia caucasica, Astragalus calycinus, A. pseudotataricus, A. bungeanus etc., which have significant value for nature protection purposes. Stony steppes's flora are an important object for biological diversity conservation and rare calcareous plants protection in the region. The habitats of rare species have scientific value. In our research we sought to emphasise regional specificity of studied communities, due to the geographical, ecological and historical features of the coenotic.